2009
DOI: 10.1021/jp8087995
|View full text |Cite
|
Sign up to set email alerts
|

Crystallite Size Dependence of Lithium Intercalation in Nanocrystalline Rutile

Abstract: An electrochemical investigation has been undertaken into the dependence of particle size on the mechanism of lithium intercalation in rutile. A thoroughly characterized suite of rutile nanoparticles with diameters in the broad size range 4-50 nm was used in the study. Variation in the cyclic voltammetry of rutile over cycling is presented for the first time and numerous new electrode reactions identified. While a crystallite size effect was witnessed during fast voltammetry experiments, this effect disappeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 68 publications
5
27
0
Order By: Relevance
“…In addition to this the high initial specific capacity may also be attributed to the formation of an SEI layer. [19] Further to this, specific capacities greater than the theoretical capacity of TiO2 (168 mAh/g for Li0.5TiO2) have previously been reported over the first 20 cycles for nanocrystalline rutile TiO2 [17] and over the first 40 cycles for rutile TiO2 submicroboxes. [5] Yu et al suggested that the high capacities obtained for the initial cycles may be related to the hollow structure of their submicroboxes, which provides more surface active sites for lithium storage and other irreversible side reactions on nanosized rutile such as the irreversible reaction with residual water.…”
Section: Structural Characterizationsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition to this the high initial specific capacity may also be attributed to the formation of an SEI layer. [19] Further to this, specific capacities greater than the theoretical capacity of TiO2 (168 mAh/g for Li0.5TiO2) have previously been reported over the first 20 cycles for nanocrystalline rutile TiO2 [17] and over the first 40 cycles for rutile TiO2 submicroboxes. [5] Yu et al suggested that the high capacities obtained for the initial cycles may be related to the hollow structure of their submicroboxes, which provides more surface active sites for lithium storage and other irreversible side reactions on nanosized rutile such as the irreversible reaction with residual water.…”
Section: Structural Characterizationsupporting
confidence: 57%
“…The two broad peaks centred at ~ 1.54 and 1.67 V and the strong peak at 2.00 V correspond to the removal of Li + from LiχTiO2. [17] All three cathodic peaks were observed in all of the successive scans, with little variation in peak potentials. The strong oxidation peak observed at 2.00 V in the initial cathodic scan shifted slightly to 2.01 V in the tenth scan.…”
Section: Structural Characterizationmentioning
confidence: 88%
“…At such a high temperature of 800°C for 3 h, surprisingly, anatase TiO 2 still exists (sample P-c), which we ascribed to the stabilizing effect of phosphate ions and the inhibition effect of conversion into the rutile phase by phosphate, as discussed above. By increasing the P/Ti molar ratio, anatase disappeared completely and vestigial broad peak appeared around 1.38 V as a result of formation of traces of rutile TiO 2 [70], this rutile traces could not be detected by XRD.…”
Section: Resultsmentioning
confidence: 96%
“…In particular, no obviously plateau-like feature is seen in all the charge curves of 3D rutile TiO 2 nanostructures for the lithium-ion insertion-extraction process at current density of 0.6 C, which is similar to the previous report about the electrochemical phenomena of other TiO 2 polymorphs for LIBs. [46] The CV tests are also performed. As presented in Fig.…”
Section: Electrochemical Performancesmentioning
confidence: 99%